گرنگترین کاریگەریە خراپەکانی تۆڕەکۆمەڵایەتیەکان لەسەر کۆمەڵگادا بە بەکارهێنانی شیکردنەوەی هۆکاری "Analysis Factor" - علي، إسراء مؤيد; عبدالله، كوجر محمد (جامعة صلاح الدين, 2022)
الشبكات التواصل الاجتماعية هي وسيلة للتكنولوجيا المستخدمة في عالم اليوم، ويوما بعد يوم يرى العلم مجموعة متنوعة من التقدم الذي يستفيد منه البشر في بعض الأحيان ويخسرونه في بعض الأحيان. وقد تم إجراء هذا البحث لتحديد أهم الآثار السلبية للشبكات الاجتماعية على المجتمع باستخدام تحليل العاملي، ولهذا الغرض، يتم توزيع استمارة الاستبيان لجمع البيانات بشكل عشوائي على خيار البحث، وتشمل الدراسة 200 مواطن، وتتراوح عمر الأفراد بين (18-48) سنة، والنسبة الذكور (43.5%) والنسبة الإناث (56.5%). في هذه الدراسة يستخدم طريقة المكونات الرئيسة، ولتلخيص الأسباب أخذنا آراء المواطنين حول الآثار السلبية للشبكات التواصل الاجتماعية، وعند تحليل النتائج البيانات تم التوصل أن هنالك ثمانية مركبات معنوية فسرت (60.383%) من التباين الكلي. Social networks are a method of technology used in our current world, and day after day science sees a variety of progress that humans sometimes benefit from it and sometimes a detriment. This study was conducted to determine the most important negative effects of social networks on society using Factor Analysis, and for this purpose, the questioner form on data collection is randomly divided into our research options that include 200 citizen’s, and the age of individuals in our choice are between 18 and 48 years old, the male gender rate is 43.5%, and the female gender rate is 56.5%. In this study, factor analysis is used to apply the principle component method to summarize the reasons for citizens' opinions about the side effects of social, By analyzing the results of the data, we concluded that the main reasons are eight reasons and also shows significant compounds were explained for each reason are (60.383%) of the total variance.
Keywords: الشبكات الاجتماعية -- اضرار وسائل التواصل الاجتماعي -- التحليل العاملي